Experience of morphine therapy for refractory dyspnea as palliative care in advanced heart failure patients. Issue 6 (June 2020) - Kawaguchi, Juri; Hamatani, Yasuhiro; Hirayama, Atsushi; Nishimura, Kunihiro; Nakai, Eri; Nakamura, Emi; Miyata, Michi; Kawano, Yukie; Takada, Yasuko; Anchi, Yuta; Funabashi, Sayaka; Kuroda, Kensuke; et al.
Highlights: Morphine was started at a low dose in real-world practice of advanced heart failure. Symptom scale and respiratory rate decreased after starting morphine administration. Blood pressure and heart rate did not change within 72 h after morphine therapy. Abstract: Background: In the field of palliative care, morphine is known to be effective for alleviating dyspnea in cancer patients. However, little is known regarding the safety and efficacy of morphine therapy for refractory dyspnea as palliative care in advanced heart failure (HF) patients. Methods: We retrospectively reviewed consecutive advanced HF patients who were referred to the Palliative Care Team at our institution and administered morphine for refractory dyspnea during hospitalization between September 2013 and December 2018. We investigated the details of morphine usage, vital signs, an 11-point quantitative symptom scale, and adverse events at baseline, 24 h, and 72 h after the start of treatment. Results: Morphine was administered for refractory dyspnea in 43 advanced HF patients [mean age: 73.5 years, male: 28 (65%), New York Heart Association functional class IV: 43 (100%), median left ventricular ejection fraction: 25%, median B-type natriuretic peptide level: 927 pg/ml, concurrent intravenous inotrope: 33 (77%)]. Median initial dose of morphine was 5 mg/day in both oral and intravenous administration and median duration of administration was 5 days. Significant decreases in an 11-point quantitative symptom scale [7 (5, 9) vs. 2 (1, 6); p < 0.01, (data available in 8 patients)] and respiratory rate (22.2 ± 6.1 vs. 19.7 ± 5.2 breaths per minute; p < 0.01) were observed 24 h after the start of morphine administration. Meanwhile, oxygen saturation, blood pressure, and heart rate were not significantly altered after treatment (NS). Common adverse events were delirium (18%) and constipation (8%); however, no lethal adverse event definitely related to morphine therapy occurred during treatment. Conclusions: This single-center retrospective study revealed the clinical practice of morphine therapy and suggested that morphine therapy might be feasible for refractory dyspnea as palliative care in advanced HF patients.